Low-carbon hydraulic cementitious material and preparation method thereof
Patent Information
- Application Number
- CN202611500378.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-24
- Publication Date
- 2026-10-30
AI Technical Summary
[0003]磷石膏是湿法磷酸生产过程中产生的工业副产物,产量大、堆存成本高,将磷石膏经改性后用于胶凝材料,可部分替代水泥熟料,从而降低熟料用量和碳排放,但磷石膏中常含有可溶性磷、氟及有机杂质,直接掺入水泥中易导致凝结时间异常、强度降低和体积稳定性不良,此外,现有水硬性胶凝材料在强度、凝结时间和抗腐蚀性能之间难以平衡,抗水侵蚀和抗碳化稳定性也有待提高,限制了产品的使用效率,基于此,本发明对其进一步的改进处理
本发明采用改性的磷石膏配合填充剂,降低水泥熟料用量,有利于降低碳排放,同时通过特定工艺制成的改性的磷石膏、填充剂加入到产品中,有利于协调改进产品的强度、凝结时间、抗腐蚀性能、抗水侵蚀和抗碳化稳定性,通过原料之间的共配改进,产品的性能得到平衡协调改进。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of cementitious materials technology, specifically to a low-carbon rigid cementitious material and its preparation method. Background Technology
[0002] Hydraulic cementitious materials are fundamental materials in the construction industry, with silicate cement playing a dominant role. The traditional production of silicate cement requires calcining raw materials such as limestone at high temperatures, resulting in high energy consumption and large carbon emissions. Under my country's "dual carbon" strategy, the cement industry has been included in the national carbon emission trading market. How to reduce the carbon emissions of cementitious materials has become a major issue that the industry urgently needs to address. At the same time, there are a large number of energy-saving equipment in the industrial sector, such as energy-saving ovens, which can be utilized. The rational application of these devices in the preparation process of cementitious materials can reduce production energy consumption.
[0003] Phosphogypsum is an industrial byproduct generated during the wet-process phosphoric acid production process. It has a large output and high storage costs. After modification, phosphogypsum can be used in cementitious materials to partially replace cement clinker, thereby reducing clinker usage and carbon emissions. However, phosphogypsum often contains soluble phosphorus, fluorine, and organic impurities. Directly adding it to cement can easily lead to abnormal setting time, reduced strength, and poor volume stability. In addition, existing hydraulic cementitious materials have difficulty balancing strength, setting time, and corrosion resistance. Their resistance to water erosion and carbonization also needs to be improved, which limits the efficiency of product use. Based on this, the present invention further improves it. Summary of the Invention
[0004] In view of the deficiencies of the prior art, the purpose of this invention is to provide a low-carbon rigid cementitious material and its preparation method, so as to solve the problems mentioned in the background art.
[0005] The present invention solves the technical problem by adopting the following technical solution: This invention provides a low-carbon water-hardening cementitious material, comprising a matrix cementitious material, modified phosphogypsum, a filler, and water; wherein the mass ratio of the matrix cementitious material, modified phosphogypsum, filler, and water is (7~11):(2~3):(3~5):6.
[0006] Preferably, the matrix cement is PO42.5 silicate cement, wherein the PO42.5 silicate cement is also mixed with 1-3% water-reducing agent, which is a polycarboxylate water-reducing agent.
[0007] Preferably, the specific preparation method of the modified phosphogypsum is as follows: S01, calcine the phosphogypsum in an oven first, and after calcineation, cool it to room temperature for later use; Preparation of SO2-modified alumina whiskers; S03, mix 2-5 parts of 3-glycidyl etheroxypropyltriethoxysilane, 1-3 parts of hydroxyl silicone oil, and 10-15 parts of bisphenol A type epoxy resin evenly, pre-react at 90-100℃ for 1 hour, then add 2-4 parts of modified alumina whiskers and 2-3 parts of nano silicon nitride and stir thoroughly to obtain additive A based on blending and compounding. 3-Glycidyl etheroxypropyltriethoxysilane possesses both epoxy groups and hydrolyzable ethoxy groups. In the pre-reaction, it can form a chemical bond with the hydroxyl groups of epoxy resin. Hydroxy silicone oil helps improve the dispersibility of inorganic fillers in resin and the flowability of the system. S04, add 5-10 parts of the phosphogypsum prepared in S01 to 20-30 parts of anhydrous ethanol, stir evenly to form a suspension, then add 5-9% of the total mass of 3-mercaptopropyltriethoxysilane prepared in S01, heat the system to 60-70℃, and stir the reaction at a constant temperature for 1-2 hours to obtain additive B based on phosphogypsum. The ethoxy group of 3-mercaptopropyltriethoxysilane hydrolyzes under the reaction conditions and undergoes dehydration condensation with the hydroxyl groups on the surface of phosphogypsum, introducing thiol active groups on the surface of phosphogypsum. S05, additive B based on phosphogypsum and additive A based on blending and compounding are mixed in a weight ratio of (11~15):4, and then stirred to react. After the reaction is completed, the mixture is filtered under reduced pressure. The filter cake is dried under vacuum at 60~80℃ for 4~6h. After stirring is completed, the mixture is filtered and dried to obtain modified phosphogypsum. The thiol groups introduced on the surface of additive B based on phosphogypsum undergo a nucleophilic ring-opening reaction with the epoxy groups of the epoxy resin in additive A, forming a thiol-epoxy chemical bond, which improves the bonding stability between the matrix raw materials.
[0008] Preferably, the calcination temperature of the calcination treatment in S01 is 170~180℃, and the calcination time is 1~2h; the stirring reaction in S05 is a stirring reaction at 60~70℃ for 0.5~1h.
[0009] Preferably, the method for preparing modified alumina whiskers is as follows: S02a, anhydrous ethanol and deionized water are mixed evenly in a weight ratio of (95~100):25 to prepare a mixture of anhydrous ethanol and deionized water; For SO2b, alumina whiskers are ultrasonically dispersed in a mixture of anhydrous ethanol and deionized water at a volume of 5 to 8 times the total volume of alumina whiskers, and then ammonia is added to adjust the pH of the system to 8.5 to 9.0. SO2c was then added, followed by 5-10% of a mixture of anhydrous ethanol and deionized water containing γ-methacryloyloxypropyltrimethoxysilane. The mixture was stirred at 60-65°C for 2-3 hours. After the reaction was completed, the mixture was filtered under reduced pressure. The resulting filter cake was washed four times with deionized water and then dried at room temperature for 18-24 hours to obtain modified alumina whiskers.
[0010] After surface treatment with γ-methacryloxypropyltrimethoxysilane, the dispersibility of alumina whiskers is improved, and they can be more evenly distributed in additive A based on blending and compounding, which helps to exert the reinforcing effect of whiskers.
[0011] Preferably, the ultrasonic power for ultrasonic dispersion is 350~450W, and the ultrasonic treatment lasts for 1 hour.
[0012] Preferably, the alumina whiskers have an average diameter of 1-3 μm and an average length of 20-50 μm; the nano-silicon nitride has a particle size of 20-100 nm and a specific surface area of 60-100 m². 2 / g.
[0013] Preferably, the filler is prepared by: S11, preheat the nano-zeolite to 110~120℃ for later use, dissolve KH-570 in ethanol to prepare a KH-570 ethanol solution with a mass percentage of 50~55%. S12, spray KH-570 ethanol solution onto the preheated nano-zeolite surface, keep stirring during the spraying process to make the nano-zeolite surface uniformly wetted by the solution. After the spraying is finished, keep the system at 80~90℃ for 1~2h to obtain surface-modified nano-zeolite. S13: 3-5 parts of sheet graphene, 4-7 parts of surface-modified nano-zeolite, 15-20 parts of ethanol solvent and 1-2 parts of 3-aminopropyltriethoxysilane are mixed and stirred at 60-70℃ for 1-2 hours, then filtered and dried to obtain the filler.
[0014] By modifying phosphogypsum through calcination activation, silane mercaptoation, and epoxy-whisker-nano silicon nitride composite, and introducing modified nano-zeolite / graphene fillers, a multi-scale organic-inorganic hybrid reinforcement system was constructed. This system utilizes phosphogypsum to replace part of the cement, achieving solid waste resource utilization and low-carbon emission reduction. The interface bonding between phosphogypsum and the cement matrix is strengthened through mercapto-epoxy chemical bonding, and water resistance is improved by epoxy coating and the hydrophobic effect of silane. The synergistic reinforcement and toughening of microfibers and nanoparticles are achieved by relying on alumina whiskers, graphene, and nano-zeolite, improving strength, crack resistance, and impermeability. At the same time, the micro-expansion of phosphogypsum hydration compensates for cement shrinkage, improving volume stability. Overall, this material has comprehensive advantages in terms of low carbon and environmental protection, mechanical properties, durability, and volume stability.
[0015] Preferably, the nano-zeolite has a particle size of 20-80 nm and a specific surface area of 300-500 m². 2 / g; the sheet-like graphene has a sheet diameter of 1~10μm and a thickness of 1~5nm.
[0016] This invention also provides a method for preparing a low-carbon rigid cementitious material, comprising the following steps: Weigh the raw materials according to the weight proportions, mix the base cement, modified phosphogypsum, filler and water evenly, mix at a speed of 150~250 r / min for 1 hour, after mixing is completed, pour into shape, and then cure naturally for 7~10 days to obtain low-carbon water-hard cementitious material.
[0017] Compared with the prior art, the present invention has the following beneficial effects: This invention uses modified phosphogypsum in combination with fillers to reduce the amount of cement clinker used, which is beneficial to reducing carbon emissions. At the same time, the modified phosphogypsum and fillers produced by a specific process are added to the product to help coordinate and improve the product's strength, setting time, corrosion resistance, water erosion resistance and carbonation stability. Through the co-mixing and improvement of raw materials, the product's performance is balanced and coordinated. Detailed Implementation
[0018] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to specific examples. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0019] This embodiment of a low-carbon water-hardening cementitious material includes a matrix cementitious material, modified phosphogypsum, a filler, and water; wherein the mass ratio of the matrix cementitious material, modified phosphogypsum, filler, and water is (7~11):(2~3):(3~5):6.
[0020] The matrix cement material in this embodiment is PO42.5 silicate cement, wherein the PO42.5 silicate cement is also mixed with 1 to 3% water-reducing agent, which is polycarboxylate water-reducing agent.
[0021] The specific preparation method of the modified phosphogypsum in this embodiment is as follows: S01, calcine the phosphogypsum in an oven first, and after calcineation, cool it to room temperature for later use; Preparation of SO2-modified alumina whiskers; S03, mix 2-5 parts of 3-glycidyl etheroxypropyltriethoxysilane, 1-3 parts of hydroxyl silicone oil, and 10-15 parts of bisphenol A type epoxy resin evenly, pre-react at 90-100℃ for 1 hour, then add 2-4 parts of modified alumina whiskers and 2-3 parts of nano silicon nitride and stir thoroughly to obtain additive A based on blending and compounding. S04, add 5-10 parts of the phosphogypsum prepared in S01 to 20-30 parts of anhydrous ethanol, stir evenly to form a suspension, then add 5-9% of the total mass of 3-mercaptopropyltriethoxysilane prepared in S01, heat the system to 60-70℃, and stir the reaction at a constant temperature for 1-2 hours to obtain additive B based on phosphogypsum. S05, additive B based on phosphogypsum and additive A based on blending are mixed at a weight ratio of (11~15):4, and then stirred to react. After the reaction is completed, the mixture is filtered under reduced pressure. The filter cake is dried under vacuum at 60~80℃ for 4~6h. After stirring is completed, the mixture is filtered and dried to obtain modified phosphogypsum.
[0022] In this embodiment, the calcination temperature of the calcination treatment in S01 is 170~180℃, and the calcination time is 1~2h; the stirring reaction in S05 is a stirring reaction at 60~70℃ for 0.5~1h.
[0023] The method for preparing the modified alumina whiskers in this embodiment is as follows: S02a, anhydrous ethanol and deionized water are mixed evenly in a weight ratio of (95~100):25 to prepare a mixture of anhydrous ethanol and deionized water; For SO2b, alumina whiskers are ultrasonically dispersed in a mixture of anhydrous ethanol and deionized water at a volume of 5 to 8 times the total volume of alumina whiskers, and then ammonia is added to adjust the pH of the system to 8.5 to 9.0. SO2c was then added, followed by 5-10% of a mixture of anhydrous ethanol and deionized water containing γ-methacryloyloxypropyltrimethoxysilane. The mixture was stirred at 60-65°C for 2-3 hours. After the reaction was completed, the mixture was filtered under reduced pressure. The resulting filter cake was washed four times with deionized water and then dried at room temperature for 18-24 hours to obtain modified alumina whiskers.
[0024] In this embodiment, the ultrasonic dispersion power is 350~450W, and the ultrasonic treatment lasts for 1 hour.
[0025] In this embodiment, the alumina whiskers have an average diameter of 1-3 μm and an average length of 20-50 μm; the nano-silicon nitride has a particle size of 20-100 nm and a specific surface area of 60-100 m². 2 / g.
[0026] The method for preparing the filler in this embodiment is as follows: S11, preheat the nano-zeolite to 110~120℃ for later use, dissolve KH-570 in ethanol to prepare a KH-570 ethanol solution with a mass percentage of 50~55%. S12, spray KH-570 ethanol solution onto the preheated nano-zeolite surface, keep stirring during the spraying process to make the nano-zeolite surface uniformly wetted by the solution. After the spraying is finished, keep the system at 80~90℃ for 1~2h to obtain surface-modified nano-zeolite. S13: 3-5 parts of sheet graphene, 4-7 parts of surface-modified nano-zeolite, 15-20 parts of ethanol solvent and 1-2 parts of 3-aminopropyltriethoxysilane are mixed and stirred at 60-70℃ for 1-2 hours, then filtered and dried to obtain the filler.
[0027] The nano-zeolite in this embodiment has a particle size of 20-80 nm and a specific surface area of 300-500 m². 2 / g; the sheet-like graphene has a sheet diameter of 1~10μm and a thickness of 1~5nm.
[0028] This embodiment describes a method for preparing a low-carbon rigid cementitious material, comprising the following steps: Weigh the raw materials according to the weight proportions, mix the base cement, modified phosphogypsum, filler and water evenly, mix at a speed of 150~250 r / min for 1 hour, after mixing is completed, pour into shape, and then cure naturally for 7~10 days to obtain low-carbon water-hard cementitious material.
[0029] Preparation of modified phosphogypsum (General examples 1-5): S01, calcine the phosphogypsum in an oven at 175°C for 1.5 hours. After calcination, cool it to room temperature for later use.
[0030] Preparation of SO2-modified alumina whiskers: S02a, anhydrous ethanol and deionized water are mixed evenly at a weight ratio of 98:25 to prepare a mixture of anhydrous ethanol and deionized water.
[0031] For SO2b, alumina whiskers were ultrasonically dispersed in a mixture of anhydrous ethanol and deionized water, which was 6 times the total volume of alumina whiskers. The ultrasonic power was 400W, and the mixture was ultrasonicated for 1 hour. Then, ammonia was added to adjust the pH of the system to 8.8.
[0032] S02c, then 8% of the total amount of a mixture of anhydrous ethanol and deionized water of γ-methacryloyloxypropyltrimethoxysilane was added and the mixture was stirred at 62°C for 2.5 h. After the reaction was completed, the mixture was filtered under reduced pressure, and the resulting filter cake was washed four times with deionized water and finally dried at room temperature for 20 h to obtain modified alumina whiskers.
[0033] S03, 3.5 parts of 3-glycidyl etheroxypropyltriethoxysilane, 2 parts of hydroxyl silicone oil and 12 parts of bisphenol A type epoxy resin are mixed evenly and pre-reacted at 95°C for 1 hour. Then, 3 parts of modified alumina whiskers and 2.5 parts of nano silicon nitride are added and stirred thoroughly to obtain additive A based on blending and compounding.
[0034] S04: Add 8 parts of the phosphogypsum prepared in S01 to 25 parts of anhydrous ethanol, stir evenly to form a suspension, then add 7% of the total mass of 3-mercaptopropyltriethoxysilane of the phosphogypsum prepared in S01, heat the system to 65°C, and stir at a constant temperature for 1.5 h to obtain additive B based on phosphogypsum.
[0035] S05, additive B based on phosphogypsum and additive A based on blending and compounding are mixed at a weight ratio of 13:4 and stirred at 65°C for 0.8 h. After the reaction is completed, the mixture is filtered under reduced pressure and the filter cake is dried under vacuum at 70°C for 5 h to obtain modified phosphogypsum.
[0036] Preparation of fillers (general for Examples 1-5): S11, preheat the nano-zeolite to 115℃ and set aside. Dissolve KH-570 in ethanol to prepare a 52% KH-570 ethanol solution.
[0037] S12, spray KH-570 ethanol solution onto the preheated nano-zeolite surface, stirring during the spraying process to ensure the nano-zeolite surface is uniformly wetted by the solution. After spraying, the system is kept at 85℃ for 1.5h to obtain surface-modified nano-zeolite.
[0038] S13, 4 parts of sheet graphene, 5.5 parts of surface-modified nano zeolite, 18 parts of ethanol solvent and 1.5 parts of 3-aminopropyltriethoxysilane were mixed and stirred at 65°C for 1.5 h, then filtered and dried to obtain the filler.
[0039] Example 1: Weigh the raw materials according to the following proportions by weight: 9 parts of matrix cement (PO42.5 silicate cement mixed with 2% polycarboxylate superplasticizer), 2.5 parts of modified phosphogypsum, 4 parts of filler, and 6 parts of water.
[0040] The base cementitious material, modified phosphogypsum, filler, and water are mixed evenly at a mixing speed of 200 r / min for 1 hour. After mixing, the mixture is poured into a mold and then naturally cured for 8 days to obtain a low-carbon water-hard cementitious material.
[0041] Example 2: The difference between this embodiment and Example 1 is as follows: the matrix cementitious material is 7 parts, the modified phosphogypsum is 2 parts, the filler is 3 parts, and the water is 6 parts; in the preparation of the modified phosphogypsum, the calcination temperature of SO1 is 170℃ and the calcination time is 2h; in SO3, 3-glycidyl etheroxypropyltriethoxysilane is 2 parts, hydroxyl silicone oil is 1 part, bisphenol A type epoxy resin is 10 parts, modified alumina whiskers are 2 parts, and nano-silicon nitride is 2 parts; in SO4, phosphogypsum is 5 parts, and anhydrous ethanol is... The total mass of phosphogypsum was 20 parts, and 3-mercaptopropyltriethoxysilane was 5% of the total mass of phosphogypsum; in S05, the weight ratio of additive B to additive A was 11:4, the stirring reaction temperature was 60℃, and the reaction time was 1h; in the preparation of the filler, in S13, there were 3 parts of sheet graphene, 4 parts of surface-modified nano-zeolite, 15 parts of ethanol solvent, and 1 part of 3-aminopropyltriethoxysilane; the blending speed was 150r / min, and natural curing was performed for 7d; the remaining conditions were the same as in Example 1.
[0042] Example 3: The difference between this embodiment and Example 1 is as follows: the matrix cementitious material is 11 parts, the modified phosphogypsum is 3 parts, the filler is 5 parts, and the water is 6 parts; in the preparation of the modified phosphogypsum, the calcination temperature of SO1 is 180℃ and the calcination time is 1h; in SO3, 3-glycidyl etheroxypropyltriethoxysilane is 5 parts, hydroxyl silicone oil is 3 parts, bisphenol A type epoxy resin is 15 parts, modified alumina whiskers are 4 parts, and nano-silicon nitride is 3 parts; in SO4, phosphogypsum is 10 parts, and anhydrous ethanol is... The total mass of the phosphogypsum was 30 parts, and 3-mercaptopropyltriethoxysilane was 9% of the total mass of the phosphogypsum; in S05, the weight ratio of additive B to additive A was 15:4, the stirring reaction temperature was 70℃, and the reaction time was 0.5h; in the preparation of the filler, in S13, there were 5 parts of sheet graphene, 7 parts of surface-modified nano-zeolite, 20 parts of ethanol solvent, and 2 parts of 3-aminopropyltriethoxysilane; the blending speed was 250r / min, and the natural curing time was 10d; the remaining conditions were the same as in Example 1.
[0043] Example 4: The difference between this embodiment and Example 1 is as follows: In the preparation of modified alumina whiskers, the weight ratio of anhydrous ethanol to deionized water in SO2a is 95:25; the weight ratio of alumina whiskers to the mixed solution in SO2b is 1:5, and the pH value is 8.5; the amount of γ-methacryloyloxypropyltrimethoxysilane added in SO2c is 5% of the total amount of the mixed solution, the reaction temperature is 60℃, the reaction time is 3h, and the drying is carried out at room temperature for 18h; the other conditions are the same as in Example 1.
[0044] Example 5: The difference between this embodiment and Example 1 is as follows: In the preparation of modified alumina whiskers, the weight ratio of anhydrous ethanol to deionized water in SO2a is 100:25; the weight ratio of alumina whiskers to the mixed solution in SO2b is 1:8, and the pH value is 9.0; the amount of γ-methacryloyloxypropyltrimethoxysilane added in SO2c is 10% of the total amount of the mixed solution, the reaction temperature is 65℃, the reaction time is 2h, and the drying is carried out at room temperature for 24h; the other conditions are the same as in Example 1.
[0045] Comparative Example 1: The difference between Comparative Example 1 and Example 1 is that no modification treatment of phosphogypsum was performed, while the other conditions were the same as in Example 1.
[0046] Comparative Example 2: The difference between Comparative Example 2 and Example 1 is that 3-mercaptopropyltriethoxysilane was not added to SO4 in the preparation of the modified phosphogypsum, while the other conditions were the same as in Example 1.
[0047] Comparative Example 3: The difference between Comparative Example 3 and Example 1 is that SO3 was not added to the modified phosphogypsum, which contained modified alumina whiskers and nano-silicon nitride. The other conditions were the same as in Example 1.
[0048] Comparative Example 4: The difference between Comparative Example 4 and Example 1 is that 3-glycidyl etheroxypropyltriethoxysilane and hydroxyl silicone oil were not added to SO3 in the preparation of the modified phosphogypsum, while the other conditions were the same as in Example 1.
[0049] Comparative Example 5: The difference between Comparative Example 5 and Example 1 is that no sheet graphene was added in S13 during the preparation of the filler, while the other conditions were the same as in Example 1.
[0050] Comparative Example 6: The difference between Comparative Example 6 and Example 1 is that surface-modified nano-zeolite was not added in S13 during the preparation of the filler, while the other conditions were the same as in Example 1.
[0051] Comparative Example 7: The difference between Comparative Example 7 and Example 1 is that in the preparation of the filler, S12 did not use KH-570 ethanol solution to modify the surface of the nano-zeolite, while the other conditions were the same as in Example 1.
[0052] Comparative Example 8: The difference between Comparative Example 8 and Example 1 is that γ-methacryloyloxypropyltrimethoxysilane was not added to SO2c in the preparation of the modified alumina whiskers, while the other conditions were the same as in Example 1.
[0053] Performance testing (1) Compressive strength: The compressive strength of cement mortar was tested according to GB / T17671-2021 "Test method for strength of cement mortar (ISO method)" at 3d, 7d and 28d.
[0054] (2) Setting time: The setting time was determined in accordance with GB / T1346-2011 "Standard consistency water requirement, setting time and soundness test method for cement".
[0055] (3) Flexural strength: The flexural strength was determined in accordance with GB / T17671-2021 and tested after 28 days.
[0056] (4) Carbonation resistance: The carbonation depth was determined in accordance with GB / T50082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete".
[0057] (5) Resistance to sulfate attack: The compressive strength and corrosion resistance coefficient were determined in accordance with GB / T50082-2009.
[0058] (6) Volume stability: The test shall be conducted in accordance with JC / T603-2004 "Test method for drying shrinkage of cement mortar".
[0059] Table 1. Test results of mechanical properties and setting time for each embodiment and comparative example.
[0060] Table 2. Durability test results for each embodiment and comparative example.
[0061] As can be seen from Tables 1 and 2: The 3-day compressive strength of Examples 1-5 reached 25.3-29.8 MPa, the 28-day compressive strength reached 51.5-58.2 MPa, the 28-day flexural strength reached 8.5-9.5 MPa, the initial setting time was 115-140 min, and the final setting time was 180-210 min; the 28-day carbonation depth was 2.8-4.5 mm, the sulfate resistance coefficient was 92.3-96.8%, and the 28-day drying shrinkage rate was 0.030-0.038%. This indicates that the low-carbon rigid cementitious material prepared by this invention possesses excellent mechanical properties, suitable setting time, good carbonation resistance, sulfate resistance, and excellent volume stability.
[0062] Compared to the examples, the 28-day compressive strength of Comparative Example 1 decreased to 38.2 MPa, the initial setting time increased to 210 min, the carbonization depth increased to 8.5 mm, and the drying shrinkage increased to 0.065%, indicating that the modification treatment of phosphogypsum plays a key role in improving the mechanical properties of the material, regulating the setting time, and improving durability and volume stability. The 28-day compressive strength of Comparative Example 2 decreased to 42.5 MPa, indicating that mercaptoyl modification plays an important role in strengthening the interfacial bond between phosphogypsum and the cement matrix. The properties of Comparative Examples 3 and 4 were all lower than those of the examples, indicating that the components in Additive A have a synergistic effect on improving the overall performance of the material.
[0063] The 28-day compressive and flexural strengths of Comparative Examples 5 and 6 were lower than those of the Example, with increased carbonization depth, indicating that graphene and nano-zeolite play an important role in improving the mechanical properties and carbonization resistance of the materials. The performance of Comparative Example 7 was lower than that of the Example, indicating that surface modification plays a crucial role in improving the compatibility of nano-zeolite with the matrix. The performance of Comparative Example 8 was lower than that of the Example, indicating that surface modification of alumina whiskers has a significant impact on its dispersibility and reinforcing effect in the matrix.
[0064] In summary, this invention constructs a multi-scale organic-inorganic hybrid reinforcement system by calcination activation, silane mercaptoization, and epoxy-whisker-nano silicon nitride composite modification of phosphogypsum, and by introducing modified nano zeolite / graphene fillers. This effectively solves the technical problem of balancing strength, setting time, and corrosion resistance in existing hydraulic cementitious materials, while realizing the resource utilization and low-carbon emission reduction of phosphogypsum, achieving outstanding comprehensive performance improvement.
[0065] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.
[0066] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
Claims
1. A low-carbon rigid cementitious material, characterized in that, It includes a base cementitious material, modified phosphogypsum and filler, and water; wherein the mass ratio of the base cementitious material, modified phosphogypsum and filler, and water is (7~11):(2~3):(3~5):
6.
2. The low-carbon rigid cementitious material according to claim 1, characterized in that, The matrix cement is PO42.5 silicate cement, which also contains 1-3% water-reducing agent, which is polycarboxylate water-reducing agent.
3. The low-carbon rigid cementitious material according to claim 1, characterized in that, The specific preparation method of the modified phosphogypsum is as follows: S01, calcine the phosphogypsum in an oven first, and after calcineation, cool it to room temperature for later use; Preparation of SO2-modified alumina whiskers; S03, mix 2-5 parts of 3-glycidyl etheroxypropyltriethoxysilane, 1-3 parts of hydroxyl silicone oil, and 10-15 parts of bisphenol A type epoxy resin evenly, pre-react at 90-100℃ for 1 hour, then add 2-4 parts of modified alumina whiskers and 2-3 parts of nano silicon nitride and stir thoroughly to obtain additive A based on blending and compounding. S04, add 5-10 parts of the phosphogypsum prepared in S01 to 20-30 parts of anhydrous ethanol, stir evenly to form a suspension, then add 5-9% of the total mass of 3-mercaptopropyltriethoxysilane prepared in S01, heat the system to 60-70℃, and stir the reaction at a constant temperature for 1-2 hours to obtain additive B based on phosphogypsum. S05, additive B based on phosphogypsum and additive A based on blending are mixed at a weight ratio of (11~15):4, and then stirred to react. After the reaction is completed, the mixture is filtered under reduced pressure. The filter cake is dried under vacuum at 60~80℃ for 4~6h. After stirring is completed, the mixture is filtered and dried to obtain modified phosphogypsum.
4. The low-carbon rigid cementitious material according to claim 3, characterized in that, The calcination temperature for the calcination treatment described in S01 is 170~180℃, and the calcination time is 1~2h; the stirring reaction described in S05 is a stirring reaction at 60~70℃ for 0.5~1h.
5. The low-carbon rigid cementitious material according to claim 3, characterized in that, The preparation method of modified alumina whiskers is as follows: S02a, anhydrous ethanol and deionized water are mixed evenly in a weight ratio of (95~100):25 to prepare a mixture of anhydrous ethanol and deionized water; For SO2b, alumina whiskers are ultrasonically dispersed in a mixture of anhydrous ethanol and deionized water at a volume of 5 to 8 times the total volume of alumina whiskers, and then ammonia is added to adjust the pH of the system to 8.5 to 9.
0. SO2c was then added, followed by 5-10% of a mixture of anhydrous ethanol and deionized water containing γ-methacryloyloxypropyltrimethoxysilane. The mixture was stirred at 60-65°C for 2-3 hours. After the reaction was completed, the mixture was filtered under reduced pressure. The resulting filter cake was washed four times with deionized water and then dried at room temperature for 18-24 hours to obtain modified alumina whiskers.
6. The low-carbon rigid cementitious material according to claim 5, characterized in that, The ultrasonic power for ultrasonic dispersion is 350~450W, and the ultrasonic treatment lasts for 1 hour.
7. The low-carbon rigid cementitious material according to claim 5, characterized in that, Alumina whiskers have an average diameter of 1–3 μm and an average length of 20–50 μm; nano-silicon nitride has a particle size of 20–100 nm and a specific surface area of 60–100 m². 2 / g.
8. The low-carbon rigid cementitious material according to claim 1, characterized in that, The preparation method of the filler is as follows: S11, preheat the nano-zeolite to 110~120℃ for later use, dissolve KH-570 in ethanol to prepare a KH-570 ethanol solution with a mass percentage of 50~55%. S12, spray KH-570 ethanol solution onto the preheated nano-zeolite surface, keep stirring during the spraying process to make the nano-zeolite surface uniformly wetted by the solution. After the spraying is finished, keep the system at 80~90℃ for 1~2h to obtain surface-modified nano-zeolite. S13: 3-5 parts of sheet graphene, 4-7 parts of surface-modified nano-zeolite, 15-20 parts of ethanol solvent and 1-2 parts of 3-aminopropyltriethoxysilane are mixed and stirred at 60-70℃ for 1-2 hours, then filtered and dried to obtain the filler.
9. The low-carbon rigid cementitious material according to claim 8, characterized in that, Nano-zeolites have a particle size of 20-80 nm and a specific surface area of 300-500 m². 2 / g; the sheet-like graphene has a sheet diameter of 1~10μm and a thickness of 1~5nm.
10. A method for preparing a low-carbon rigid cementitious material according to any one of claims 1 to 9, characterized in that, Includes the following steps: Weigh the raw materials according to the weight proportions, mix the base cement, modified phosphogypsum, filler and water evenly, mix at a speed of 150~250 r / min for 1 hour, after mixing is completed, pour into shape, and then cure naturally for 7~10 days to obtain low-carbon water-hard cementitious material.